Effects of Shade on Microclimate, Canopy Characteristics and Light Integrals in Dry Season Field-Grown Cocoa (Theobroma cacao L.) Seedlings - S Agele; B Famuwagun; A Ogunleye (Journal of Horticultural Sciences, 2016)
Effect of shade regimes on gradients of microclimate, canopy extent (leaf area index: LAI) and light integrals in dry season field-grown cocoa (cacao) seedlings was investigated in a rainforest zone of Nigeria. The shade regimes tested were: unshaded/open-to-sun, dense shade and moderate shade. Shade intensity affected solar radiation transmission through cacao canopy, photosynthetic active radiation (PAR) and canopy light attenuation (extinction coefficient, k). Intensity of transmitted radiation below the canopy from incident radiation was highest for open-to-sun, followed by moderate and dense shade, respectively. The temporal trend of intercepted radiation showed that intercepted radiation increased from December to May, and, the values were highest for open-to-sun, followed by moderate and dense shade. The ratio of transmitted (Io) to incident (I) radiation (IO/I) was higher for open sun. Significant differences were found between open-to-sun (unshaded) and moderate and dense shade intensity for value of canopy extinction coefficient (k). The association of growing degree days (GDD), and, total leaf number (TLN) and leaf area index (LAI), were characterized by high coefficient of determination (R2) for the respective open, dense and moderate shade treatments. Inverse of the slope of the regression of relationship between estimated thermal time (°Cdays) and corresponding total leaf number (TLN) denotes leaf appearance rate (phyllochron, in °Cdays/leaf). Rate of leaf appearance was faster in open sun compared with to that in moderate or dense shade intensity. Characteristics of the cacao canopy development were measured by leaf area index (LAI), a parameter which affects the intercepted photosynthetic active radiation (PAR). Higher LAI was obtained in no shade (open sun) compared to that in moderate or dense shade treatments. Unshaded plants had a higher radiation use efficiency (RUE) and RUE values were significantly higher compared to the other two treatments. Low light intensity and LAI for under-storey cacao had negative implications for growth and biomass development. Air temperatures within the cacao field were highest for open sun cacao, followed by moderate and dense shade, respectively; the values increased from December to April, with peak values seen in April.